Sodium Glucose Transporter 2 Inhibitors Versus Metformin on Cardiovascular and Renal Outcomes in Patients With Diabetes With Low Cardiovascular Risk: A Nationwide Cohort Study - Hao‐Chih Chang; Yun‐Yu Chen; Tzu‐Ting Kuo; Yenn‐Jiang Lin; Kuo‐Liong Chien; Hung‐Yu Chang; Chung‐Lieh Hung; Fa‐Po Chung (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background This study investigated whether initial SGLT2 (sodium‐glucose cotransporter 2) inhibitor‐based treatment is superior to metformin‐based regimens as a primary prevention strategy among low‐risk patients with diabetes. Methods and Results In this nationwide cohort study, a total of 38 496 patients with diabetes with low cardiovascular risk were identified (age 62.0±11.6 years, men 50%) from January 1 to December 31, 2016. Patients receiving SGLT2 inhibitors‐based and metformin‐based regimens were 1:2 matched by propensity score. Study outcomes included all‐cause mortality, cardiovascular death, hospitalization for heart failure, stroke, and progression to end‐stage renal disease. Compared with 1928 patients receiving metformin‐based regimens, 964 patients receiving SGLT2 inhibitor‐based regimens had similar all‐cause mortality (hazard ratio [HR], 0.75 [95% CI, 0.51–1.12]), cardiovascular death (HR, 0.69 [95% CI, 0.25–1.89]), hospitalization for heart failure (HR, 1.06 [95% CI, 0.59–1.92]), stroke (HR, 0.78 [95% CI, 0.48–1.27]), and progression to end‐stage renal disease (HR, 0.88 [95% CI, 0.32–2.39]). However, SGLT2 inhibitors were associated with a lower risk of all‐cause mortality (HR, 0.47 [95% CI, 0.23–0.99]; P for interaction=0.008) and progression to end‐stage renal disease (HR, 0.22 [95% CI, 0.06–0.82]; P for interaction=0.04) in patients under the age of 65. Conclusions In comparison to metformin‐based regimens, SGLT2 inhibitor‐based regimens showed a similar risk of all‐cause mortality and adverse cardiorenal events. SGLT2 inhibitors might be considered as first‐line therapy in select low‐risk patients, for example, younger patients with diabetes.